2023
DOI: 10.1186/s12966-023-01542-x
|View full text |Cite
|
Sign up to set email alerts
|

How the COVID-19 pandemic and related school closures reduce physical activity among children and adolescents in the WHO European Region: a systematic review and meta-analysis

Helena Ludwig-Walz,
Waldemar Siemens,
Sarah Heinisch
et al.

Abstract: Background Emerging research suggests that physical activity among children and adolescents decreased during the COVID-19 pandemic. However, a differentiated overview of European youth is lacking. In particular, no systematic analysis has been conducted to date on the impact of heterogeneous pandemic restrictions and school closures within European countries, and with regard to potentially vulnerable groups. Methods We searched seven databases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Furthermore, studies have shown that the COVID-19 pandemic may promote depression, anxiety symptoms, including children and adolescents ( 31 , 32 ). And all types of physical activity among children and adolescents had a precipitous decline during the COVID-19 pandemic ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that the COVID-19 pandemic may promote depression, anxiety symptoms, including children and adolescents ( 31 , 32 ). And all types of physical activity among children and adolescents had a precipitous decline during the COVID-19 pandemic ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, notably, 3.5% of the children attended presential class. Moreover, research shows an increase in mental health symptoms because of school closure (4,5,27). A systematic review and metaanalysis included 868,634 children and adolescents (≤ 19 years) pre-pandemic and 807,480 during the COVID-19 pandemic in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, all forms of physical activity experienced a sharp decrease among European children and adolescents during the COVID-19 pandemic. This decline was particularly noticeable during school closures and predominantly affected younger schoolchildren and adolescents (Ludwig-Walz et al, 2023).…”
Section: Introductionmentioning
confidence: 99%